Handheld Point-of-Care Ultrasound: Safety Considerations for Creating Guidelines. (September 2022) - Hsieh, Adam; Baker, Maxwell B; Phalen, Joseph M; Mejias-Garcia, Julio; Hsieh, Alan; Hsieh, Alex; Canelli, Robert
Background: Compared to traditional ultrasound machines, emerging handheld point-of-care-ultrasound (HPOCUS) systems exhibit superior portability and affordability. Thus, they have been increasingly embraced in the intensive care setting. However, there is scarce data on patient safety and current regulatory body guidelines are lacking. Here, we critically appraise the literature with a focus on the merits, concerns, and framework of existing POCUS guidelines. Subsequently, we provide recommendations for future regulatory guidelines. Methods: A comprehensive literature review was conducted using the PubMed database employing the key words "point-of-care/handheld/portable ultrasound" and "guidelines" alone, in combination, and using thesaurus terms. Eligible articles were scrutinized for description of potential benefits and concerns of HPOCUS, especially from a patient safety perspective, as well as currently existing POCUS practice guidelines. Data was extracted, reported thematically using a narrative synthesis approach, then subsequently used to guide our proposed guidelines. Results: The most widely reported benefits of HPOCUS include superior portability, affordability, imaging, facilitation of expedited diagnosis and management, and integration with medical workplace flow. However, major barriers to adoption include device security/patient confidentiality and patient safety. Furthermore, except for a policy published by the American College of Emergency Physicians (ACEP) in 2018, there are few other national regulatory guidelines pertaining to handheld POCUS. In light of this, we propose a framework for HPOCUS guideline development to address these and other concerns. Such guidelines include training and credentialing, bioengineering approval, and strategic integration with electronic medical record systems. Conclusion: HPOCUS can be a powerful tool for expedited diagnosis and management guidance. However, there is limited data regarding patient safety and current regulatory body guidelines are lacking. Our assessment illuminates that there remain many unsolved problems about HPOCUS, and in turn, we propose guidelines to address safe regulation and implementation.